2012
DOI: 10.1091/mbc.e11-12-1058
|View full text |Cite
|
Sign up to set email alerts
|

Critical role of the first transmembrane domain of Cx26 in regulating oligomerization and function

Abstract: This study identifies a motif within the first transmembrane domain of Cx26, from amino acids Val-37 through Ala-40, that is critical for oligomerization and function. The impacts of deafness-associated mutations within this motif upon gap junction channel and hemichannel functions correlate with the severity of disease that they cause.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
52
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(68 citation statements)
references
References 42 publications
14
52
0
2
Order By: Relevance
“…21,27 However, biochemical and electrophysiological studies of cell lines showed that p.V37I reduced the oligomerization efficiency of Cx26, the protein encoded by GJB2, and significantly compromised the channel function of gap junctions. 28 Consistent with the experiments in cell lines, several clinical studies supported that homozygosity for p.V37I is associated with mild to moderate SNHI in humans. 23,[29][30][31][32] Analyses based on serial audiometric data in children with bi-allelic GJB2 mutations further revealed that, among a wide variety of different GJB2 mutations, progression of SNHI was particularly common among carriers of p.V37I either in homozygosity or in compound heterozygosity with another GJB2 mutation.…”
Section: Discussionsupporting
confidence: 69%
“…21,27 However, biochemical and electrophysiological studies of cell lines showed that p.V37I reduced the oligomerization efficiency of Cx26, the protein encoded by GJB2, and significantly compromised the channel function of gap junctions. 28 Consistent with the experiments in cell lines, several clinical studies supported that homozygosity for p.V37I is associated with mild to moderate SNHI in humans. 23,[29][30][31][32] Analyses based on serial audiometric data in children with bi-allelic GJB2 mutations further revealed that, among a wide variety of different GJB2 mutations, progression of SNHI was particularly common among carriers of p.V37I either in homozygosity or in compound heterozygosity with another GJB2 mutation.…”
Section: Discussionsupporting
confidence: 69%
“…Maeda et al (124) speculate that the extracellular half of TM2 and TM4 and the extracellular loops are likely to form the protein/protein interfaces that allow Cx subunits to oligomerize into hexameric connexons (homo-/heteromeric interactions), since these regions contain most of the interaction sites of Cx subunits. However, using TOXCAT assays to study the interaction of isolated transmembrane ␣-helices, Jara et al (76) very recently identified a critical role of the first transmembrane domain of Cx26, and specifically of residues V 37 VAA 40 , in regulating Cx-dimerization, hexamer formation, and channel function. The extracellular loops (E1, E2) of two connected hemichannels (homo-/heterotypic interactions) form concentric, antiparallel ␤-barrels, which make a tight seal in the extracellular space between the opposing PMs (48, 147,199) (FIGURE 2, B AND C).…”
Section: The 3d Structure Of a Gj Channel Provides Functional Cues Rementioning
confidence: 99%
“…According to the crystal structure of Cx26, the first transmembrane domain is the major pore-lining helix that is involved in prominent intraconnexin interactions with all other transmembrane domains to stabilize the basic structure of the connexin subunit (Maeda et al, 2009). In addition, the V37 amino acid is located in a motif, 37 VVAA 40 , that is conserved between Cx26 and Cx30 (Maeda et al, 2009;Smith et al, 2002), and, as demonstrated by the V37I Cx26 mutant, mutations within this particular motif reduce hexamer formation and channel function (Jara et al, 2012). Importantly, the V37E Cx30 mutation involves a unique and crucial substitution of a glutamic acid residue for a hydrophobic valine, which we propose alters crucial intraconnexin interactions and Cx30 stability, resulting in improper folding and protein accumulation in the ER.…”
Section: The Loss-of-function V37e Mutant Linked To Clouston and Kidmentioning
confidence: 99%